Towards developing Web Online Public Access Catalog with Interactive Map (WOCMAP) for Perpustakaan Tun Abdul Razak 4, Universiti Teknologi MARA, Shah Alam / Fazlon Samak - Samak, Fazlon (2006)
This research project is about constructing an interactive map for developing an enhancement of Web Online Public Access Catalog. The objectives of this research are to identify the requirements of interactive map for Web Online Public Access Catalogue (WebOPAC), to design an interactive map and web online catalogue system and to demonstrate the interactive map in WebOPAC. The researcher use three approaches in gathering information about online catalog and interactive map; by conducting informal interviews with the end users (patrons), conducting formal interviews with the stakeholder and through studying recent researches by past researchers. These informal interviews are done by the researcher asked questions based on the set of questionnaires that have been prepared earlier. This is used for getting the requirements for new web online catalog and to defined interactive features need to be adapted. By conducting the formal interviews with the stakeholder, the researcher intend to know the flow and processes involved while cataloging the new book. It is also to understand the current system that has been used by the PTAR 4. The researcher also studying recent researches by past researchers in defming interactive map features and observing the existing web online that apply the interactive map to get some ideas on interface design and to build the prototype to prove and to be revised by the end-user and stakeholder. From the findings, researcher foimd that the standard that has been used. Library Congress Subject Headings (LCSH) part of Library of Congress Classification (LCC) that has been introduced by Library of Congress, to shelving the books is suitable for adapting the interactive map. Map on web can be classifies into two; static map and dynamic map. Map that has been used for this research is floor plan map. This is because the floor plan maps show the structure building of each level. Based fi-om the past researches, there are several features that shows the map is interactive of not. After successfully develop the web online catalog using an interactive map, the researcher found that all approaches for developing the interactive map and web online catalog has been done and therefore, all the objectives in this research project have been achieved.